2019
DOI: 10.1021/acs.analchem.9b01259
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Peptide Fractionation and Native Digestion as Two Novel Sample Preparation Workflows to Improve HCP Characterization by LC–MS/MS

Abstract: Host cell proteins (HCPs) are the predominant class of impurities during manufacturing of therapeutic proteins. Previous reports have successfully shown that HCP characterization by LC–MS/MS ultimately leads to drug products of superior safety and quality. Here, we present two sample preparation strategies to approach the wide dynamic range required and compared them systematically to a standard protocol. First, we describe PreOmics fractionation as an effective 2D offline strategy. Second, we evaluate an alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…All of the results in this publication are from analyses performed using a native digestion method adapted from the method published by Huang et al 22 This method has come into more frequent use in industry due to its simplicity and ability to reliably identify HCP down to low ppm levels, depending on the LC-MS system used. [22][23][24][25] To more accurately describe the levels of individual HCP identified across multiple protein therapeutics analyzed, all the results are given in a mole ratio ppm (micromoles of HCP compared to moles of antibody) rather than the traditional mass ratio ppm (nanogram of HCP compared to milligram of antibody) used in ELISAbased HCP analysis. Use of ppm in mole ratio allows a fairer comparison of the actual abundance of different HCP identified by taking into consideration the fact that different HCP usually have a wide range of molecular weights (MW).…”
Section: Data Compilationmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the results in this publication are from analyses performed using a native digestion method adapted from the method published by Huang et al 22 This method has come into more frequent use in industry due to its simplicity and ability to reliably identify HCP down to low ppm levels, depending on the LC-MS system used. [22][23][24][25] To more accurately describe the levels of individual HCP identified across multiple protein therapeutics analyzed, all the results are given in a mole ratio ppm (micromoles of HCP compared to moles of antibody) rather than the traditional mass ratio ppm (nanogram of HCP compared to milligram of antibody) used in ELISAbased HCP analysis. Use of ppm in mole ratio allows a fairer comparison of the actual abundance of different HCP identified by taking into consideration the fact that different HCP usually have a wide range of molecular weights (MW).…”
Section: Data Compilationmentioning
confidence: 99%
“…In this paper, we performed the HCP analysis for over two dozen commercially available mAb-based therapeutics (Table 1) produced in Chinese hamster ovary (CHO) cell lines by LC-MS/MS. [22][23][24] Individual HCP across these approved biopharmaceuticals were identified and their abundance was estimated. We also summarized the MS-based HCP analysis results from the past several years of biotherapeutics development done in house.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, very high product titers compared to low levels of HCPs is the main challenge for samples obtained during the DSP and the final product, and solutions to this problem, like peptide fractionation or native digestion of the HCPs without denaturation of the drug product, have been published. [36][37][38] Furthermore, antigen-binding affinities and immunogenic HCP concentrations, limitation of anti-HCP antibody species and nonspecific binding to the IAC materials (e.g., column or beads), must be considered. Therefore, a suitable control strategy for nonspecific HCP binding is indispensable.…”
Section: Iac Of Hcp Immunogen and Dspmentioning
confidence: 99%
“…As an orthogonal method, liquid chromatography coupled to tandem mass spectrometry (LC‐MS/MS) evolved as a powerful technique to provide the identity and (relative) quantity of present HCPs (Walker et al, 2017). The capabilities of state‐of‐the‐art LC‐MS/MS workflows to analyze a HCP standard were demonstrated in a recent study leading to >1000 identified HCPs (Huang et al, 2017; Kufer et al, 2019). 2D DIGE (Figure 1a) remains the prevalent method (83%) for evaluating the similarity between the HCP antigen and the production harvest, but also LC‐MS/MS (30%) plays a significant role.…”
Section: Main Textmentioning
confidence: 99%